Conservation of Australia's Forest Fauna 2004
DOI: 10.7882/fs.2004.048
|View full text |Cite
|
Sign up to set email alerts
|

Research for Ecologically Sustainable Forest Management in Victorian eucalypt forests

Abstract: This paper describes some of the research needed to help forest managers achieve Ecologically Sustainable Forest Management. As a case study, it also presents an overview of some of the research conducted to meet those needs in the state of Victoria, and identifies priorities for further research, monitoring and adaptive management. Vertebrate wildlife (mainly birds and mammals) has been a major focus of this review. The main strategic research questions concern the successional effects of logging, the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 133 publications
(157 reference statements)
0
12
0
Order By: Relevance
“…Subsequent studies in BoxIronbark forests have shown that more large old trees were flowering at a given time than young trees (Wilson and Bennett, 1999). Previous studies have shown that honeyeaters tend to be more common in old than young forest (Loyn, 1985c(Loyn, , 2004. Provision of cavities has been a focus of several studies in Australia (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequent studies in BoxIronbark forests have shown that more large old trees were flowering at a given time than young trees (Wilson and Bennett, 1999). Previous studies have shown that honeyeaters tend to be more common in old than young forest (Loyn, 1985c(Loyn, , 2004. Provision of cavities has been a focus of several studies in Australia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Forest managers accept the need to maintain old trees at suitable distributions in the landscape, but need information to guide them in making strategic decisions at the scale of individual stands and the broader forest landscape (Loyn, 1985a(Loyn, , 2004Gibbons et al, 2002;Lindenmayer and Franklin, 2002). The issue is a challenge because wood production is greatest at the younger stages of stand development, and deliberate retention of old trees on coupes and old stands in the landscape (and younger trees and stands to replace them over time) are likely to be needed (Loyn, 1985a).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations